“Gestión del talento humano y su incidencia en el mejoramiento del desempeño laboral de las pequeñas Farmacias del sector el Guayacán Quevedo 2023” - Garcés Mora , Marlene Rosario (2024)
The objective of this research project is to evaluate the human talent management of small pharmacies in the Guayacán sector. The problem is the management of human talent in the recruitment of personnel, retention that affects performance. The research is descriptive and field research, the methods used were deductive, inductive and analytical: the techniques to be used are survey and interview to the administrators and employees of the pharmacy. The population consisted of 27 employees and administrators from 7 pharmacies in the El Guayacán sector: Distrifarma, two Cruz Azul, La Primicia, Santa Martha, Sana Sana and Económica. The results showed that the Human Talent Management practices in the pharmacies are weak due to inadequate management of human talent management processes, from admission, retention, compensation, incentives, work environment, which negatively affects the work performance of employees. In conclusion, there are weaknesses and strengths that should be exploited in actions that describe the activities to be managed in order to implement improvements in the pharmacies.